2016
DOI: 10.1016/j.kjms.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal pelvic pressure and postoperative fever incidence between standard‐ and mini‐tract percutaneous nephrolithotomy

Abstract: This study was proposed to compare the clinical effectiveness of mini-tract percutaneous nephrolithotomy (MPCNL) with standard-tract percutaneous nephrolithotomy (SPCNL) and verify whether MPCNL is associated with both higher renal pelvic pressure (RPP) and incidence of postoperative fever. A total of 228 patients with kidney stone were randomly allocated to the MPCNL group (n=114) and SPCNL group (n=114). Both intraoperative and postoperative indexes along with the incidence of complications were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 26 publications
1
49
0
3
Order By: Relevance
“…To reduce the morbidity associated with this procedure, miniaturized PCNL systems were developed [3][4][5][6]. However, these systems present some limitations such as a more difficult stone fragments retrieval, a smaller visual field, longer operative times (OT) and higher intrarenal pressures (IRPs) [7,8]. In particular, IRP higher than 30 mmHg (40.78 cmH 2 O) has been proven to cause pyelovenous backflow [9], potentially leading to infectious complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the morbidity associated with this procedure, miniaturized PCNL systems were developed [3][4][5][6]. However, these systems present some limitations such as a more difficult stone fragments retrieval, a smaller visual field, longer operative times (OT) and higher intrarenal pressures (IRPs) [7,8]. In particular, IRP higher than 30 mmHg (40.78 cmH 2 O) has been proven to cause pyelovenous backflow [9], potentially leading to infectious complications [10].…”
Section: Introductionmentioning
confidence: 99%
“…Omar et al evaluated the impact of irrigation pressures in standard PCNL on risk of systemic inflammatory response syndrome (SIRS) and observed that high-pressure fluid irrigation was a risk factor for postoperative SIRS [35]. Chu et al focused specifically on the differences between standard and mini PCNL and found comparatively higher intrarenal pressures for mini PCNL, and also noted that mini PCNL procedures were more likely to be associated with postoperative sepsis [36]. In a porcine model, mini PCNL was associated with higher intrarenal pressures and higher risk of organ bacterial seeding in the setting of an infected collecting system, suggesting a higher potential for infectious complications [37].…”
Section: Safety Aspects Of Lithotripsy During Miniaturized Pcnlmentioning
confidence: 99%
“…Duration (>60 s) of raised renal pelvic pressure >30 mmHg also predicts the chances of postoperative fever, irrespective of the tract size. [1] Guo et al . in 2008 reported that higher intrapelvic pressures >30 mmHg for >10 min is associated with higher incidence of complications during mini-PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…measured the IRPs during standard (24 Fr) and mini-PCNL (18 Fr) and found that pressures >30cm of H2O were a risk factor for postoperative fever. [1] Tokas et al . found that during mini-PCNL the IRPs ranged from 10 to 45 cm of water.…”
Section: Introductionmentioning
confidence: 99%